DEVELOPMENT OF INSTRUMENTS FOR ASSESSING HIGHER-ORDER THINKING SKILLS (HOTS) PHYSICS IN HIGH SCHOOL (LITERATURE REVIEW) - Nurmaliati, Nurmaliati; Ilwandri; Tomi Apra santosa (Indonesia Journal of Engineering and Education Technology (IJEET), 2025)
Higher-order thinking skills (HOTS) are a student's abilities that include logical and reasoning abilities, analysis, evaluation, and creation. This study aims to identify the development of instruments for assessing higher-order thinking skills (HOTS) in Physics in high school. This review uses a qualitative approach by examining journals from 2016 to 2020. Based on the results of the analysis, show that one form of assessment developed is test questions with multiple choice, reasoned multiple choice, and description-type instruments. The test questions were developed to pay attention to HOTS, KKO indicators, physics, and stimulus problems, as well as Bloom's taxonomy. The materials that are widely developed are temperature and heat, harmonic vibrations, and static and dynamic fluids. The methods often used in this development research are the R&D method from Brog and Gall, the 4D method, the qualitative descriptive method, and the ADDIE method. The HOTS instrument is carried out through a feasibility test and analysis process, including through a validity test by a validator, reliability test, difficulty level test, differential power test, Rasch model analysis, analysis using Cronbach's Alpha formula, and question distractor test. The results of this study are an illustration of important points related to how to develop instruments for assessing higher-order thinking skills(HOTS) in Physics in high school